Juridical Analysis Of The Effectiveness Of Termination Of Prosecutions Based On Restorative Justice - Oki Bogitama; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2021)
The purpose of this research is to find out and analyze the effectiveness of stopping prosecutions based on restorative justice. To find out and analyze the process of discontinuing prosecution for termination based on restorative justice in terms of the principles of restorative justice. The approach method used in this research is a sociological juridical method (Sociological Research).Based on the results of this study it was concluded that effectiveness of the termination of prosecution based on Restorative Justice is carried out by taking into account the interests of the victims and other protected legal interests; avoidance of negative stigma; avoidance of retaliation; community response and harmony; and propriety, decency, and public order. The process of discontinuing prosecution based on restorative justice has met the requirements of the principle of restorative justice, namely that the Public Prosecutor offers peace efforts to Victims and Suspects. The Public Prosecutor shall summon the Victim legally and appropriately by stating the reason for the summons. In the event that it is deemed necessary, peace efforts may involve the families of the Victim/Suspect, community leaders or representatives, and other related parties. The Public Prosecutor shall notify the aims and objectives as well as the rights and obligations of the Victims and Suspects in peace efforts, including the right to refuse peace efforts. In the event that the peace effort is accepted by the Victim and the Suspect, the peace process will be continued.